Age-Related Diagnostic Considerations and Neurocognitive Impairment Implications for Insomnia Disorder - Gencarelli, Amy M (East Carolina University, 2023)
Insomnia affects 10-30% of the U.S. population and can be found across varying stages of life. While it has previously been shown that the addition of quantitative indices would be helpful for distinguishing between sleep disturbances and insomnia, it begs the question if quantity-derived thresholds vary throughout the lifespan. One of the major current diagnostic systems utilized in the U.S. (the DSM-5) acknowledges quantitative indices being useful in identifying cases of insomnia and that daytime impairment is necessary for a diagnosis of insomnia. This study aims to see how these two factors, may vary by age, sex, and/or race as well as if standardized objective neurocognitive measures can better assess for daytime impairment than self-report.
Keywords: Neurocognitive; Insomnia--Diagnosis--United States; Insomnia--Age factors--United States; Sleep--Age factors--United States